Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Mie Gacoan di Tangerang Selatan - Pane, Mutiara Wibowo; Ali, Sampor (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study is titled The Effect of Product Quality and Service Quality on Consumer Satisfaction of Mie Gacoan in Tangerang Selatan. The purpose of this research is to determine the effect of product quality and service quality on consumer satisfaction of Mie Gacoan in Tangerang Selatan. This research employs a quantitative method with an associative approach. The population in this study consists of consumers who have purchased Mie Gacoan products in South Tangerang. The sampling technique used is non-probability sampling, with a sample size of 100 respondents who are Mie Gacoan consumers. The data analysis in this study is conducted using IBM SPSS 21 software. Data collection is carried out through a questionnaire distributed via Google Forms to Mie Gacoan consumers in Tangerang Selatan. The results of this study indicate that the product quality variable has a positive and significant effect on consumer satisfaction, with a partial test significance result of 0.000. Similarly, the service quality variable also has a positive and significant effect on consumer satisfaction, with a partial test significance value of 0.001. Furthermore, simultaneously, the product quality and service quality variables have a significant effect on consumer satisfaction, as shown by the F-test result with a significance value of 0.000.